Safety and efficacy of His-Purkinje system pacing in the treatment of patients with atrial fibrillation and heart failure: a systematic review and meta-analysis - Guan, Lin; Wang, Chuanhe; Guan, Xueqing; Cheng, Gong; Sun, Zhijun (Frontiers in Cardiovascular Medicine, 2023)
Aim: To evaluate the safety and efficacy of the His-Purkinje system pacing (HPCSP) in the treatment of individuals with atrial fibrillation (AF) complicated by heart failure (HF).The PubMed, Cochrane Library, Web of Science, and Embase databases were searched through September 1, 2022. The literature was initially screened based on the inclusion and exclusion criteria. The baseline characteristics of the subjects, implantation success rate, New York Heart Association (NYHA) classification, left ventricular ejection fraction (LVEF), left ventricular end-diastolic diameter (LVEDd), QRS duration, pacing threshold, and impedance were extracted and summarized; statistical analysis was performed using RevMan 5.3 software.Results: In all, 22 articles were included, involving 1445 patients. Compared to biventricular pacing (BiVP), HPCSP resulted in improved cardiac function, including increased ejection fraction (MD=5.69, 95% CI:0.78-10.60, P=0.02) and decreased LVEDd (MD =−3.50, 95%CI:−7.05-0.05, P=0.05). It was also correlated with shorter QRS duration (MD=−38.30, 95%CI: −60.71-−15.88, P<0.01) and reduced all-cause mortality and rehospitalization events (RR=0.72, 95% CI:0.57-0.91, P<0.01) in patients. Left bundle branch pacing (LBBP) lowered the pacing threshold (MD=0.47; 95% CI:0.25-0.69; P<0.01), and there was no statistical difference in the rate of endpoint events when comparing these two physiologic pacing modalities(RR=1.56, 95% CI:0.87-2.80, P=0.14).The safety and efficacy of HPCSP in patients with AF and HF were verified in this meta-analysis. HPCSP can reverse cardiac remodeling and has great clinical application value. Relatively speaking, His-bundle pacing (HBP) can maintain better ventricular electro-mechanical synchronization, and the pacing parameters of LBBP are more stable.